The Biodiversity of Fish Fauna in GobardhanDas Pond (Saran District), North Bihar - Prabhat Ranjan (International Journal on Orange Technologies, 2020)
Biodiversity defines the capacity and trophic status of any aquatic environment. In particular for the protection and management of inland water supplies including rivers, reservoirs and wetlands, it is very important to have adequate knowledge of the constituent biota. The present study explores the diversity of fish fauna found in Saran district saran Gobardhan Das pond. In the Gobardhan Das pond of Saran district Saran the richness of fish fauna has never been recorded. The goal of the study was to evaluate and analyse the variety and the abundance of the important fish fauna in the Gobardhan Das pond, in Saran district of Saran, between January 2008 and December 2009. We recorded and identified 17 Gobardhan DasSaran district saran freshwater fish species that belonged to three orders, 6 families and 9 generations. Nine species were Cyprinidae, 3 were Channidae, 3 were Bagridae, and the remaining Clariidae, E, Heteropneustidae, and Osphronemidae were described by only single species. Among these are 9 species belonging to the Cyprinidae family. Proper documentation leading to a diversity information system is desperately needed in order to protect the diversity of fish and establish sustainable fishing practises. The article also explains the structure of the population with its relative contributions and some significant results that may better explain the current ichthyofaunal diversity scenario.The findings of our study would therefore provide valuable information on the biodiversity of the GobardhanDas Pond fish fauna that would be valuable for systematic management and conservation of fishing